1998
DOI: 10.1080/03079459808419332
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of polyvinylpolypyrrolidone on aflatoxicosis in broilers

Abstract: This study was conducted in order to evaluate the efficiacy of a polyvinylpolypyrrolidone for protection against aflatoxicosis in broiler chicks. For this purpose 132 day-old broiler chicks (Hybro) were used. They were divided into four groups, each of 33 chicks. Group 1: control; Group 2: 3 g of polyvinylpolypyrrolidone (PVPP) per kg of diet; Group 3: 2.5 mg of aflotoxin (AF) per kg of diet; Group 4: 2.5 mg of AF per kg of diet plus 3 g of PVPP per kg of diet. The chicks were maintained on these treatments fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 12 publications
4
15
0
1
Order By: Relevance
“…These results support our findings that aflatoxin causes normocytic normochromic anaemia. Moreover, the results of Kiran et al (1998), who stated that aflatoxin B 1 causes a depletion of lymphoid cells, supported our findings regarding the lymphocytopenia and monocytopenia in aflatoxin-treated rats. There was a significant increase in the WBC count, which mainly consisted of neutrophils.…”
Section: Resultssupporting
confidence: 94%
“…These results support our findings that aflatoxin causes normocytic normochromic anaemia. Moreover, the results of Kiran et al (1998), who stated that aflatoxin B 1 causes a depletion of lymphoid cells, supported our findings regarding the lymphocytopenia and monocytopenia in aflatoxin-treated rats. There was a significant increase in the WBC count, which mainly consisted of neutrophils.…”
Section: Resultssupporting
confidence: 94%
“…Ozen et al (2009) stated a dose-dependent vascular degeneration in liver cells in aflatoxicosis that was a sign of fat accumulation. In this study, we observed vacular degeneration similar to previous reports (Kiran et al, 1998;Ozen et al, 2009). It was reported that vacular degeneration could be due to impaired lipid transport rather than increases lipid biosynthesis (McLean & Dutton, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…An increase in WBC and heterophile counts in the present study shows that aflatoxin may elicit an inflammatory response in the chickens as Kececi et al (1998) observed by 2.5 mg/kg aflatoxin application into diet. It has been also demonstrated that aflatoxin caused lymphoid cells depletion in the bursa of Fabricius and thymus (Kiran et al 1998). In consistent with this experiment Keçeci et al (1995) reported that aflatoxicosis caused lymphocytopenia and heterophilia in growing chickens.…”
Section: Treatmentssupporting
confidence: 76%